Brain-computer interface with somatosensory feedback improves functional recovery from severe hemiplegia due to chronic stroke - Ono, Takashi; Shindo, Keiichiro; Kawashima, Kimiko; Ota, Naoki; Ito, Mari; Ota, Tetsuo; Mukaino, Masahiko; Fujiwara, Toshiyuki; Kimura, Akio; Liu, Meigen; Ushiba, Junichi (Frontiers in Neuroengineering, 2014)
Recent studies have shown that scalp electroencephalogram (EEG) based brain-computer interface (BCI) has a great potential for motor rehabilitation in stroke patients with severe hemiplegia. However, key elements in BCI architecture for functional recovery has yet to be clear. We in this study focused on the type of feedback to the patients, which is given contingently to their motor-related EEG in a BCI context. The efficacy of visual and somatosensory feedbacks was compared by a two-group study with the chronic stroke patients who are suffering with severe motor hemiplegia. All the patients were asked an attempt of finger opening in the affected side repeatedly, and the event-related desynchronization (ERD) in EEG of alpha and beta rhythms was monitored over bilateral parietal regions. Six patients were received a simple visual feedback in which the hand open/grasp picture on screen was animated at eye level, following significant ERD. Eight patients were received a somatosensory feedback in which the motor-driven orthosis was triggered to extend the paralyzed fingers from 90 to 50 degrees. All the participants received 1-h BCI treatment with 12-20 training days. After the training period, while no changes in clinical scores and electromyographic (EMG) activity were observed in visual feedback group after training, voluntary EMG activity was newly observed in the affected finger extensors in 4 cases and the clinical score of upper limb function in the affected side was also improved in 5 participants in somatosensory feedback group. Although the present study was conducted with a limited number of patients, these results imply that BCI training with somatosensory feedback could be more effective for rehabilitation than with visual feedback. This pilot trial positively encouraged further clinical BCI research using a controlled design.